Mediation effects of attitudes on the generational and gender influence on Swiss General Practitioners’ home visits: a cross-sectional study (Swiss Medical Weekly, 2025)
BACKGROUND: In family medicine, home visits are a tangible manifestation of patient-centred care, allowing physicians to comprehensively understand patients’ circumstances and cater to their medical and psychosocial needs. However, a recent decline in general practitioner home visits has raised significant concerns about the potential impact on care quality, particularly for older patients. General practitioners’ age, gender and attitudes may play a role. Attitudes refer to positive or negative thinking or feelings about something typically reflected in a person’s behaviour.AIMS: To study the effects of age and gender (i.e. predictors) on the number of home visits conducted during a typical week of work (i.e. outcome) by general practitioners in Canton Ticino, Switzerland. To investigate whether attitudes (i.e. mediators) mediate the relationship between age and home visits, controlling for gender.METHODS: A cross-sectional study was conducted from June to October 2023 on 142 family doctors (28% women) with an average age of 56.42 years (standard deviation [SD] = 11.51, range 36–83). Correlations between variables and a t-test with gender were conducted. A mediation analysis was performed to examine the potential association in which the attitudes may mediate the relationship between age and home visits, controlling for gender.RESULTS: Older physicians conducted more home visits in a typical week (r = 0.32, p